Criminal process in republican key : constitutional safeguard against situations similar to caesarium (Prudentia Iuris, 2017)
The author analyzes the Criminal Procedural Law from the perspective of Constitutional Law and especially the republican form of government. This perspective allows us to glimpse the importance of punitive law containing the constitutional guarantees and political freedoms in pursuit of the common good. At the same time, the anti-republican projections are discussed in the topic to conclude with a call to the redefinition of certain concepts such as the principle of contradiction, that of orality and the importance of rhetoric akin to the notion of poliacroasis
Keywords: Criminal procedure; Constitution; Republicanism; Contradiction’s principle; Oralidad; Poliacroasis